Executive functioning and emotion recognition in youth with oppositional defiant disorder and/or conduct disorder. (8th August 2020) - Kleine Deters, Renee; Naaijen, Jilly; Rosa, Mireia; Aggensteiner, Pascal M.; Banaschewski, Tobias; Saam, Melanie C.; Schulze, Ulrike M. E.; Sethi, Arjun; Craig, Michael C.; Sagar-Ouriaghli, Ilyas; Santosh, Paramala; Castro-Fornieles, Josefina; et al.
Abstract: Objectives: Executive functioning and emotion recognition may be impaired in disruptive youth, yet findings in oppositional defiant disorder (ODD) and conduct disorder (CD) are inconsistent. We examined these functions related to ODD and CD, accounting for comorbid attention-deficit/hyperactivity disorder (ADHD) and internalising symptoms. Methods: We compared executive functioning (visual working memory, visual attention, inhibitory control) and emotion recognition between youth (8–18 years old, 123 boys, 55 girls) with ODD ( n = 44) or CD (with/without ODD, n = 48), and healthy controls ( n = 86). We also related ODD, CD, and ADHD symptom counts and internalising symptomatology to all outcome measures, as well as executive functioning to emotion recognition. Results: Visual working memory and inhibitory control were impaired in the ODD and CD groups versus healthy controls. Anger, disgust, fear, happiness, and sadness recognition were impaired in the CD group; only anger recognition was impaired in the ODD group. Deficits were not explained by comorbid ADHD or internalising symptoms. Visual working memory was associated with recognition of all basic emotions. Conclusions: Our findings challenge the view that neuropsychological impairments in youth with ODD/CD are driven by comorbid ADHD and suggest possible distinct neurocognitive mechanisms in CD versus ODD.